Liquid Organic Fertilizer Products From Eggshell Waste For Grade X High School Students - Indah Adelia Soraya; Tri Wahyu Agustina; Sri Hartati; Mar’atus Solikha (FKIP - Universitas Riau, 2026)
Environmental pollution caused by household organic waste requires contextual and solution oriented learning. This study aims to analyze the quality of liquid organic fertilizer (LOF) made from eggshell waste through the application of E-STREAM Project-Based Learning (PjBL) on environmental pollution. The study employed a quasi experimental method using a Posttest Only Non Equivalent Control Group Design involving 60 tenth grade students at SMAN 1 Sukakarya, consisting of 30 students in the experimental class and 30 students in the control class. Data were collected using observation sheets and a product assessment rubric, and were analyzed using quantitative descriptive analysis to evaluate the implementation of learning and the quality of students' LOF products. The results showed that the implementation of learning was categorized as very good, with teacher activity reaching 98.03% and student activity reaching 86.76%. The average quality of LOF products in the experimental class was 93.50% (very good), which was higher than that of the control class at 82.33% (good). These findings indicate that E-STREAM based PjBL can improve the quality of students' products and provides an alternative contextual PjBL approach for biology and environmental education.